2016
DOI: 10.1002/tea.21369
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous science engagement: A family self‐ethnography

Abstract: While opportunities for spontaneous, undesigned, serendipitous science engagement (SSE) are abundant and evidence regarding its affordances is accumulating, little is known about its nature. In this paper, I present a model defining and identifying SSE, which consists of a personal and a contextual continuum. To explore the nature of family SSE, I analyzed a 66‐minute case, obtained through self‐ethnography, of three children and a mother engaging with bugs they discovered in their backyard. Employing the “lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Vedder‐Weiss () has suggested a model for classifying engagement in informal settings that accounts for both choice and structure. We use this model to classify the different settings in the museum.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Vedder‐Weiss () has suggested a model for classifying engagement in informal settings that accounts for both choice and structure. We use this model to classify the different settings in the museum.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Thus, people identify and are identified as members or nonmembers of a community (or as a “kind of person,” Gee, , p. 99) through their interaction with others. To study science identity in family life, I therefore take the family to be a community of practice, in which children are novices participating in scientific practices alongside their parents (or siblings), who may act as experts (Vedder‐Weiss, ). Through such shared participation, the children learn the family's science practice and shape their science identities.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…The analysis revealed that over the course of the year, the family engaged with science in a wide array of settings, from educationally designed settings, such as visits to science centers and zoos, to undesigned settings (Vedder‐Weiss, ), such as dinnertime and strolling in the streets (Table ). Scientific content (Table ) also varied significantly, including all STEM domains (Biology, Chemistry, Physics, Technology, Engineering, and occasionally also Math) and focusing on both abstract objects (e.g., a discussion of the concept of gravity) and concrete objects (e.g., a dry patch spotted in the grass during a walk to the store).…”
Section: Data and Findingsmentioning
confidence: 99%
See 2 more Smart Citations